How does online streaming affect antitrust remedies to centralized marketing? The case of European football broadcasting rights - Oliver Budzinski; Sophia Gänßle; Philipp Kunz-Kaltenhäuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2019)
The collective sale of football broadcasting rights constitutes a cartel, which, in the European Union, is only allowed if it complies with a number of conditions and obligations, inter alia, partial unbundling and the no-single-buyer rule. These regulations were defined with traditional TV-markets in mind. However, the landscape of audiovisual broadcasting is quickly changing with online streaming services gaining popularity and relevance. This also alters the effects of the conditions and obligations for the centralized marketing arrangements. Partial unbundling may lead to increasing instead of decreasing prices for consumers. Moreover, the combination of partial unbundling and the no-single-buyer rule forces consumers into multiple subscriptions to several streaming services, which increases transaction costs. Consequently, competition authorities need to rethink the conditions and obligations they impose on centralized marketing arrangements in football. We recommend restricting the exclusivity of (live-)broadcasting rights and mandate third-party access to program guide information to redesign the remedies.
Keywords: Z20; Z21; Z28; K21; L40; L83; L82; 330; collective sale of broadcasting rights; sports economics; antitrust; competition policy; centralized marketing; sports and media; football; online media